PASAR IKAN BERSIH SUKADANA, KABUPATEN KAYONG UTARA - Muhammad Khairul; Hamdil Khaliesh; Emilya Kalsum (JMARS: Jurnal Mosaik Arsitektur, 2023)
North Kayong Regency is in the fishing area in WPP 711 which is the cumulative management area of the Karimata Strait, Natuna Sea and South China Sea areas, which allows this district to have large production potential in the fisheries sector. The potential of the fisheries sector in the large North Kayong Regency has not been fully utilized optimally due to the low availability of facilities and infrastructure for handling catches. As the capital of a district that has high potential for fish production, Sukadana does not yet have adequate catch handling facilities, so it is necessary to have facilities for fishermen and consumers, especially for the people of North Kayong Regency. The design of the Sukadana Clean Fish Market, Kayong Utara Regency aims to facilitate both in the food and economic sectors for the people of North Kayong Regency. The method used is the glass box method, which goes through several stages starting from collecting data related to fish market issues, identifying problems in the fish market, then obtaining theories related to clean fish markets as fish market standards based on relevant regulations, formulating design concepts, conducting analysis , then make pre-design drawings and technical drawings (DED). Through the design concept of a hygienic fish market in Sukadana District, Kayong Utara Regency, a fish market combines traditional market systems and modern markets which is presented in an open stall and a closed stall. The fish market with this concept was created by considering the needs and habits of the surrounding community which functions as a forum or place for buying and selling transactions as well as a place for processing fish and seafood.